Comprehensive Analysis of MYB Gene Family and Their Expressions Under Abiotic Stresses and Hormone Treatments in Tamarix hispida - Zhang, Tengqian; Zhao, Yulin; Wang, Yucheng; Liu, Zhongyuan; Gao, Caiqiu (Frontiers in Plant Science, 2018)
The MYB family is one of the most abundant transcription factor families in plants. MYB proteins are involved in plant development, abiotic stress tolerance and hormone signal transduction, etc. However, there are few studies on the MYB transcription factor family and its regulatory mechanism in Tamarix hispida. In this study, 14 MYB genes (named ThMYB1 - ThMYB14) were cloned and characterized from T. hispida. The expression profiles of ThMYBs in T. hispida roots and leaves under different abiotic stress conditions were monitored using real-time quantitative reverse-transcribed polymerase chain reaction (qRT-PCR). The results showed that most of the ThMYBs were significantly upregulated and/or downregulated by salt and osmotic stress, ABA, GA3 and JA treatments in at least one organ. Especially, ThMYB13 was upregulated in the roots and leaves of T. hispida under NaCl treatment at all study periods, indicating that it may involved in salt stress in plants. To further study the function of ThMYB13, transgenic T. hispida plants with overexpression or knockdown of ThMYB13 and an empty pROKII vector (as the control) were generated using a transient transformation system. Under salt stress, overexpression of ThMYB13 in T. hispida plants showed the lowest O2-, H2O2 and MDA accumulation, minimal cell death, the most stable K+/Na+ ratio and the lowest electrolyte leakage rate among the three kinds of transient expression in T. hispida. Conversely, the RNAi-silencing, transiently transformed plants displayed the opposite physiological changes. These results suggest that ThMYB13 may play an important physiological role in salt stress tolerance in transgenic T. hispida plants.